Practical enterprise risk management a business process approach - Duckert, Gregory H., 1949- (Wiley, 2011)
"The book emphasizes an enterprise risk management approach that utilizes actual business data to estimate the probability and impact of key risks in an organization. While the approach is anlytical, the author has boiled it down to make it accessible to line managers and high level executives alike. The key lessons involve basing risk estimates and prevention techniques on known quantities rather then subjective estimates, which many popular ERM methodologies consist of. It will include practical examples from various industries that demonstrate key concepts, implementation guidance to get started, and tables of risk indicators and metrics, physical structure diagrams, and graphs. Tentative Table of Contents: Chapter 1 Corporate Governance: What a Mess Chapter 2 What ERM Is And What It Is Not; Chapter 3 Understanding What the Business Is; Chapter 4 Defining What True Business Risk Is; Chapter 5 Objectively Defining Risk; Chapter 6 Building a Fluid/Dynamic Risk Model; Chapter 7 The Strategy: Evolving The Fluid Risk Model; Chapter 8 The Future Evolution of the Model; Chapter 9 Related Topics and Special Risk Situations; Chapter 10 Maximizing Impact - Minimizing Exposure"